2018
DOI: 10.48550/arxiv.1805.08810
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Habitability Classification of Exoplanets: A Machine Learning Insight

Abstract: We explore the efficacy of machine learning (ML) in characterizing exoplanets into different classes. The source of the data used in this work is University of Puerto Rico's Planetary Habitability Laboratory's Exoplanets Catalog (PHL-EC). We perform a detailed analysis of the structure of the data and propose methods that can be used to effectively categorize new exoplanet samples. Our contributions are two fold. We elaborate on the results obtained by using ML algorithms by stating the accuracy of each method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Explicit Earth-similarity score computation (Bora et al, 2016) based on parameters mass, radius, surface temperature and escape velocity developed into Cobb-Douglas Habitability Score helped identify candidates with similar scores to Earth. However, using Earth-similarity alone (Agrawal et al, 2018) to address habitability is not sufficient unless model based evaluations (Saha et al, 2018c) are interpreted and equated with feature based classification (Basak et al, 2018). However, when we tested methods in (Basak et al, 2018), it was found that the methods didn't work well with pruned feature sets (features which clearly mark different habitability classes were removed).…”
Section: Classification Of Exoplanetsmentioning
confidence: 99%
See 4 more Smart Citations
“…Explicit Earth-similarity score computation (Bora et al, 2016) based on parameters mass, radius, surface temperature and escape velocity developed into Cobb-Douglas Habitability Score helped identify candidates with similar scores to Earth. However, using Earth-similarity alone (Agrawal et al, 2018) to address habitability is not sufficient unless model based evaluations (Saha et al, 2018c) are interpreted and equated with feature based classification (Basak et al, 2018). However, when we tested methods in (Basak et al, 2018), it was found that the methods didn't work well with pruned feature sets (features which clearly mark different habitability classes were removed).…”
Section: Classification Of Exoplanetsmentioning
confidence: 99%
“…However, using Earth-similarity alone (Agrawal et al, 2018) to address habitability is not sufficient unless model based evaluations (Saha et al, 2018c) are interpreted and equated with feature based classification (Basak et al, 2018). However, when we tested methods in (Basak et al, 2018), it was found that the methods didn't work well with pruned feature sets (features which clearly mark different habitability classes were removed). Therefore, new machine learning methods to classify exoplanets are a necessity.…”
Section: Classification Of Exoplanetsmentioning
confidence: 99%
See 3 more Smart Citations